Spinorial discrete symmetries and adjoint structures - Hoff da Silva, J. M. [UNESP]; Bueno Rogerio, R. J.; Quinquiolo, N. C.R. [UNESP] (Elsevier, 2022)
Extending the investigations about the theory of duals, we analyze duals built up with the aid of discrete symmetry operators. We scrutinize algebraic and physical constraints (encompassing them in a theoretical scope) in order to verify which combination of discrete symmetries may compose a physical and mathematical well-posed spinorial dual. In this scenario, we relate the Lounesto classification with several other spinor classification possibilities, attempting to connect classes and physical constraints. Several possibilities are investigated.
Keywords: Adjoint structure; Dirac spinors; Discrete symmetries; Elko spinors; Lounesto classification; Adjoints; Dirac spinor; Discrete adjoints; Discrete symmetry; Elko spinor; Physical constraints; Spinors